Immobilization of trace heavy metals in the electrokinetics-processed municipal solid waste incineration fly ashes and its characterizations and mechanisms. (15th February 2019) - Huang, Tao; Zhang, Shuwen; Liu, Longfei
Abstract: The mass production of municipal solid waste incineration (MSWI) fly ashes has caused severe concerns in regarding to the inherently ecological harm and the decreasing landfilling space. To relieve the heavy metal contamination into the environment and complete a closed-loop electrokinetics (EK), the sequential effects of electrokinetics and alkali activating solidification/stabilization (S/S) technique on the immobilization of HMs in the remnant of MSWI fly ashes were investigated in the research. The compressive strength for the remnant-based solidified product at the proposing time of 18 days was 2.58 MPa, 104.76% higher than that of the MWSI-based specimen with the optimal curing parameters being adopted for the production of the solidified matrices. The leaching concentrations of Zn, Pb, and Cu were 9.74, 0.21, and 0.75 mg/L, correspondingly reduced by 57.84%, 80.19%, and 17.58%, respectively. The opposite correlation between the compressive strength and the leaching concentration was demonstrated for both two groups of the curing samples. The mechanism results showed that the electrokinetics had significantly changed the micromorphology characteristics of MSWI fly ashes and distinctly affected the whole curing process. The cementation and geo-polymerization were comprehensively determined as two of main mechanisms for the immobilization of HMs in the curing matrices. Graphical abstract: Image 1 Highlights: A closed-loop treatment was constructed by solidifying the electrokinetic remnant. Electrokinetics enhances the polycondensation reactions of silica and alumina. An intrinsic shortage of Al source in the fly ashes controls the curing keynote. Cementation and geo-polymerization determine the immobilization of heavy metals.